PENDIDIKAN KEPEMIMPINAN DALAM KEKAWIN NÄªTIÅšÄ€TRA BAGI REMAJA HINDU - Seriadi, Si Luh Nyoman (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2020)
The younger generation is the successor of the nation who has an interest in determining the future and integrity of the Indonesian nation. Therefore, the importance of fostering leadership education for the younger generation must be instilled early on given the increasingly widespread immoral cases that occur in society. In connection with the alignment of the basic values of character education with the values contained in Hinduism, character formation can be echoed based on the concept of NÄ«tiÅ›Ästra leadership in Hinduism. The value of character education that can be realized is religion, social care, responsibility, peace of mind, hard work, democracy, and discipline.